THE INFLUENCE OF BUDGETARY PARTICIPATION, DECENTRALIZATION, ORGANIZATIONAL COMMITMENT, AND INTERNAL CONTROL SYSTEMS ON THE MANAGERIAL PERFORMANCE OF REGIONAL GOVERNMENT APPARATUSES - Palahiyah Palahiyah; Shoma Febriyani; Indina Dhesta Nugrahaeni (Amal Insani Foundation, 2022)
This study aims to determine the effect of budgetary participation, decentralization, organizational commitment, and internal control systems on the managerial performance of regional government apparatuses. This study uses quantitative research methods, The population in this study was Structural officials of the Regional Apparatus Work Unit (SKPD) in Banten Province, Indonesia, The sample selection in this study was based on purposive sampling. This study distributed 170 questionnaires. Of these, 87 questionnaires were returned of respondents returned. Data were analyzed based on multiple regression and path analysis (Analysis Path) utilizing the SPSS program. Data were analyzed used the Statistical Package for Social Science (SPSS). The data processed were respondents' answers related to Budgetary Participation (PA), Decentralization (D), Organizational Commitment (KO), Internal Control System (SPI), and Managerial Performance (KM). Based on the results obtained in hypothesis 1, there is a significant effect of budgetary participation on managerial performance of regional government apparatuses, the result of tcount> ttable (2,136> 1,456) with a significance level of 0.36 (0.00 <0,05) this means that if budgetary participation increases it will improve managerial performance, hypothesis 2 there is a significant influence of decentralization on managerial performance in Structural officials of the Regional Apparatus Work Unit (SKPD) in Banten Province, Indonesia, the result of tcount> ttable (1,999> 1,456) with a significance level of 0.049 (0.00 <0.05) this means that if decentralization increases it will improve managerial performance, hypothesis 3 there is a significant effect of organizational commitment on managerial performance of regional government apparatuses, the result of tcount> ttable (2,409> 1,456) with a significance level of 0.18 (0.00 <0,05) this means that if organizational commitment increases it will improve managerial performance, and hypothesis 4 there is a significant effect of internal control system on managerial performance of regional government apparatuses, the result of tcount> ttable (3,038> 1,456) with a significance level of 0.03 (0.00 <0,05) this means that if internal control system increases it will improve managerial performance.